Decrease in heart adrenoceptor gene expression and receptor number as compensatory tool for preserved heart function and biological rhythm in M(2) KO animals - Benes, Jan; Varejkova, Eva; Farar, Vladimir; Novakova, Martina; Myslivecek, Jaromir (Naunyn-Schmiedeberg's archives of pharmacology, 2012)
Muscarinic receptors (MR) are main cardioinhibitory receptors. We investigated the changes in gene expression, receptor number, echocardiography, muscarinic/adrenergic agonist/antagonist changes in heart rate (HR) and HR biorhythm in M(2) KO mice (mice lacking the main cardioinhibitory receptors) in the left ventricle (LV) and right ventricle (RV). We hypothesize that the disruption of M(2) MR, key players in parasympathetic bradycardia, would change the number of receptors with antagonistic effects on the heart (β(1)- and β(2)-adrenoceptors, BAR), while the function of the heart would be changed only marginally. We have found changes in LV, but not in RV: decrease in M(3) MR, β(1)- and β(2)-adrenoceptor gene expressions that were accompanied by a decrease in MR and BAR receptor binding. No changes were found both in LV systolic and diastolic function as assessed by echocardiography (e.g., similar LV end-systolic and end-diastolic diameter, fractional shortening, mitral flow characteristics, and maximal velocity in LV outflow tract). We have found only marginal changes in specific HR biorhythm parameters. The effects of isoprenaline and propranolol on HR were similar in WT and KO (but with lesser extent). Atropine was not able to increase HR in KO animals. Carbachol decreased the HR in WT but increased HR in KO, suggesting the presence of cardiostimulatory MR. Therefore, we can conclude that although the main cardioinhibitory receptors are not present in the heart, the function is not much affected. As possible mechanisms of almost normal cardiac function, the decreases of both β(1)- and β(2)-adrenoceptor gene expression and receptor binding should be considered.
Keywords: Receptors, Adrenergic, beta-2; Bradycardia; Protein Binding; Male; karbachol; Atropine; Gene Expression Regulation; mužské pohlaví; propranolol; Mice; bradykardie; srdeční komory; funkce levé komory srdeční; Heart Rate; myši knockoutované; regulace genové exprese; srdeční frekvence; isoprenalin; zvířata; Receptor, Muscarinic M2; receptor muskarinový M2; vazba proteinů; Heart Ventricles; Mice, Knockout; atropin; myši; Receptors, Adrenergic, beta-1; Carbachol; Propranolol; Isoproterenol; beta-1-adrenergní receptory; beta-2-adrenergní receptory; Ventricular Function, Left; Animals